Advancing the African Continental Free Trade Area (AfCFTA): Lessons from the Southern African Development Community Protocol on Trade - Vambe, Beauty (Comparative and International Law Journal of Southern Africa, 2024)
The African Continental Free Trade Area (AfCFTA) was founded to integrate Africa’s regional economies into a single framework of trade liberalisation. However, some scholarly works suggest that the AfCFTA threatens the existence of Africa’s Free Trade Areas (FTAs) and Regional Economic Communities (RECs). Other critics suggest that the AfCFTA overlaps with the FTAs and the objectives of Africa’s RECs. In this article, I ask how the AfCFTA can sidestep the challenges experienced by RECs such as the Southern African Development Community (SADC). What legal frameworks has the AfCFTA introduced that further entrench the legal provisions found in Africa’s FTAs and RECs? This article advances a legal view that Africa’s RECs are the building blocks of the AfCFTA. While the AfCFTA may reproduce some of the trade provisions of FTAs and RECs, overlapping can have positive effects on bilateral trade relations with RECs. In addition, the AfCFTA has leveraged processes of regional economic integration to expand markets for RECs. This article exposes the interface between the SADC Protocol on Trade and the AfCFTA protocols. A qualitative approach based on a literature review of paper and internet sources and legal documents is used to argue that the AfCFTA has drawn lessons—both positive and negative—from the efforts of regional economic blocs in Africa to achieve flexible trade integration.